2015
DOI: 10.1111/jwas.12176
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the 26S Proteasome S7 Subunit Gene and Its Expression during Regeneration in Apostichopus japonicus

Abstract: The 26S proteasome, which includes 20S core and 19S regulatory particles, plays an important role in removing harmful and/or unnecessary proteins. In this study, we cloned a 2443‐bp full‐length cDNA sequence of the S7 subunit of 19S from the sea cucumber Apostichopus japonicus, including a 70‐bp 5′‐untranslated region (UTR) and 1070‐bp 3′‐UTR coding for a theoretical 435 amino acid protein. Sequence analysis showed that S7 belongs to the ATPases associated with a wide variety of cellular activities (AAA+) supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Ginanova (2007) reported that the coelomic epithelium of the body wall and the coelomic epithelium of the muscle of A. japonicus are involved in the regeneration of muscle tissue at the same time and have an important role in the recruitment of myogenic cell pools. The work by Qin et al (2015) illustrates that the S7 subunit of the 19S gene or the S7based assembled 26S proteasome may be involved in the regulation of cell migration and cell cycle during the regeneration of the A. japonicus body wall.…”
Section: Research On the Regeneration Of Apostichopus Japonicusmentioning
confidence: 99%
“…Ginanova (2007) reported that the coelomic epithelium of the body wall and the coelomic epithelium of the muscle of A. japonicus are involved in the regeneration of muscle tissue at the same time and have an important role in the recruitment of myogenic cell pools. The work by Qin et al (2015) illustrates that the S7 subunit of the 19S gene or the S7based assembled 26S proteasome may be involved in the regulation of cell migration and cell cycle during the regeneration of the A. japonicus body wall.…”
Section: Research On the Regeneration Of Apostichopus Japonicusmentioning
confidence: 99%